2010
DOI: 10.3945/jn.109.111526
|View full text |Cite
|
Sign up to set email alerts
|

Economic Contextual Factors, Food Consumption, and Obesity among U.S. Adolescents

Abstract: Adolescents have poor dietary behaviors and high overweight prevalence. Economic contextual factors such as food prices and food store and restaurant availability are hypothesized and increasingly being explored empirically as contributors to the obesity epidemic. Evidence showed that healthful compared with less healthful foods increasingly cost more and that fast food restaurants are increasingly available. In addition, racial, ethnic, and socioeconomic disparities have been documented in access to food outl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 37 publications
3
72
1
1
Order By: Relevance
“…Consistent with previous research, 15,20,35 children living in areas with higher-priced fruits and vegetables averaged higher measures of standardized BMI scores, compared with their peers in areas with lowerpriced fruits and vegetables. We found that these associations are driven by changes in the prices of fresh fruits and vegetables rather than frozen or canned.…”
Section: Discussionsupporting
confidence: 77%
“…Consistent with previous research, 15,20,35 children living in areas with higher-priced fruits and vegetables averaged higher measures of standardized BMI scores, compared with their peers in areas with lowerpriced fruits and vegetables. We found that these associations are driven by changes in the prices of fresh fruits and vegetables rather than frozen or canned.…”
Section: Discussionsupporting
confidence: 77%
“…However, prior studies have produced conflicting findings regarding children's dining choices and weight gain. Some found no association between children's weight gain and differential exposure to food outlets [74][75][76][77][78]. Others found that increased fast food access [79][80][81] or a higher ratio of fast food to full-service restaurants [81] was associated with a higher BMI.…”
Section: Discussionmentioning
confidence: 99%
“…7-8). Similar to Obama and her colleagues' fight to provide healthy food to children of all families (especially those at or below the poverty line), lower-and middleincome neighborhoods in general have 1.25-1.3 times more fast-food restaurants than do the higher income neighborhoods (Lydon et al, 2011;Powell, Han, & Chaloupka, 2010). The authors discussed the reengineering of environments, such that the foods that are more readily available in all neighborhoods are the ones more likely to produce healthier, better balanced meals.…”
Section: Leadership Practicesmentioning
confidence: 99%